Development of recommendations on the hierarchy of activities regarding the implementation of the BRC standard in relation to the safety of packaging using the AHP method - Agnieszka Kawecka (PC Technology Center, 2021)
The British Retail Consortium Global Standard for Food Safety enjoys great popularity among food industry companies, the number of companies with the certified standard is rising every year. The packaging used for food packaging has a very large impact on the safety and quality of the packaged food. The purpose of the study was to indicate the requirements of the standard in relation to packaging, which should be implemented firstly by enterprises of the food industry. In the research part, the AHP analysis was conducted on the basis of the experts' recommendations. Decision matrixes for every criterion: hazard analysis concerning packaging, purchase procedure, packaging acceptance procedure were developed. A decision matrix for the main criterion as a result of criteria decision matrix was developed, global decision hierarchy was also developed. Research clearly showed that the most important activity (among the proposed) is hazard analysis, with a 0.517 weighted sum value. In many of the detailed requirements of the standard, hazard analysis and risk assessment (0.333 weighted sum value) are the basis for many activities, including establishing a purchasing procedure (0.163 weighted sum value), accepting packaging (0.297 weighted sum value), or many others. The relevance of this study is the identification of the hierarchy of importance of activities performed within the framework of ensuring the quality and safety of food packaging. A reasonable approach is presented. The AHP method allows indicating the sequence of activities during the implementation of the BRC standard, as evidenced by pilot studies carried out on the basis of procedures related to the safety of packaging. The standard sets up requirements for packaging in the form of packaging management procedure, in which it should be stated how the site operates with packaging. Moreover, there are requirements concerning hazard analysis in relation to packaging